2016
DOI: 10.1038/eye.2016.48
|View full text |Cite
|
Sign up to set email alerts
|

Glucose variability and inner retinal sensory neuropathy in persons with type 1 diabetes mellitus

Abstract: Purpose To quantify early neuroretinal alterations in patients with type 1 diabetes mellitus (T1DM) and to assess whether glycemic variability contributes to alterations in neuroretinal structure or function. Methods Thirty patients with T1DM and 51 controls underwent comprehensive ophthalmic examination and assessment of retinal function or structure with frequency doubling perimetry (FDP), contrast sensitivity, dark adaptation, fundus photography, and optical coherence tomography (OCT). Diabetic participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 37 publications
(51 reference statements)
4
28
0
Order By: Relevance
“…These findings indicate that glucose is a fundamental energy substrate in conditions of ischemia and that the ability of the retina to metabolically compensate during periods of low oxygen availability is impaired by low levels of blood glucose, although this is advantageous in terms of delaying the progression of diabetic retinopathy [37]. Therefore, our results confirm the hypothesis that the hypoglycemic excursions may be associated with retinal neurodegeneration [13]. Moreover, we also demonstrate that GV evaluated as CONGA, but not HbA1c, was positively associated with INL thickness, suggesting that an increase in intraday glycaemic variation seems to be involved in the development of an early activation of Müller cells.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…These findings indicate that glucose is a fundamental energy substrate in conditions of ischemia and that the ability of the retina to metabolically compensate during periods of low oxygen availability is impaired by low levels of blood glucose, although this is advantageous in terms of delaying the progression of diabetic retinopathy [37]. Therefore, our results confirm the hypothesis that the hypoglycemic excursions may be associated with retinal neurodegeneration [13]. Moreover, we also demonstrate that GV evaluated as CONGA, but not HbA1c, was positively associated with INL thickness, suggesting that an increase in intraday glycaemic variation seems to be involved in the development of an early activation of Müller cells.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, Bandello F et al [21] reported that the increase in retinal thickness occurring in macular edema was predominantly located in the INL and extended to neighboring retinal layers in Type 2 DM patients. On the other hand, it has been recently showed a modest and selective reduction in the inner region of the INL in the temporal quadrant in Type 1 DM persons with no or mild RD [13], as well as in the pericentral area of macula in patients with minimal DR [22]. The subtle differences in the macular thickness described in these studies may be explained by the fact that the progressive phenomenon of retinal neurodegeneration was “photographed” in slightly different time phases, but with significantly different findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, glycemic control estimates are steady state measures whereas blood glucose concentrations often fluctuate widely in patients. Emerging evidence suggests that excess glycemic variability influences the risk of cardiac autonomic neuropathy and mild retinopathy 13, 14 .…”
Section: Pathophysiology Of Diabetic Retinopathymentioning
confidence: 99%
“…First of all new insulin therapy technologies have been developed and implemented, such as personal insulin pumps integrated with continuous glucose monitoring systems (CGM) [14, 15]. Data from clinical trials and immunological studies point at the very important role of even minor blood glucose fluctuations in the development of both micro- and macrovascular complications [1517]. …”
Section: Introductionmentioning
confidence: 99%